Study on the Individual Coloring Mechanism of Iridescent Cells in the Mantle of the Boring Giant Clam, Tridacna crocea - Li, Yunqing; Zhou, Yinyin; Wei, Jinkuan; Shi, Gongpengyang; Liao, Qingliang; Guo, Shuming; Zhou, Zihua; Li, Jun; Qin, Yanping; Ma, Haitao; Yu, Ziniu; Zhang, Yuehuan (Frontiers in Marine Science, 2022)
Giant clams are marine bivalves that inhabit Indo-Pacific coral reefs. The boring giant clam, Tridacna crocea, exhibits bright and conspicuous mantle coloration based on the specialized cells (iridocytes) that generate structural colors. In order to illustrate the coloring mechanism of individual iridocytes, the reflection spectra curve of iridocytes was obtained by a micro-hyperspectral imager. TEM images were obtained to show the inner nanostructures of iridocytes. FDTD simulation was conducted to analyze the relationship between the color of iridocytes and the unique lamellar structure. We found that the laminae in the regular arrangement within cells govern the coloration of individual iridocytes. With the gradual increase of lamellar thickness and spacing, the color of the structure varies from bright violet to orange-red, forming a full visible spectrum. This study provides a new understanding of the various colors produced by individual iridocytes.